Klotho deficiency is an early biomarker of renal ischemia–reperfusion injury and its replacement is protective - Hu, Ming-Chang; Shi, Mingjun; Zhang, Jianning; Quiñones, Henry; Kuro-o, Makoto; Moe, Orson W. (Kidney international, 2010)
Klotho is an antiaging substance with pleiotropic actions including regulation of mineral metabolism. It is highly expressed in the kidney and is present in the circulation and urine but its role in acute kidney injury (AKI) is unknown. We found that ischemia–reperfusion injury (IRI) in rodents reduced Klotho in the kidneys, urine, and blood, all of which were restored upon recovery. Reduction in kidney and plasma Klotho levels were earlier than that of neutrophil gelatinase-associated lipocalin (NGAL), a known biomarker of kidney injury. Patients with AKI were found to have drastic reductions in urinary Klotho. To examine whether Klotho has a pathogenic role, we induced IRI in mice with different endogenous Klotho levels ranging from heterozygous Klotho haploinsufficient, to wild-type (WT), to transgenic mice overexpressing Klotho. Klotho levels in AKI were lower in haploinsufficient and higher in transgenic compared with WT mice. The haploinsufficient mice had more extensive functional and histological alterations compared with WT mice, whereas these changes were milder in overexpressing transgenic mice, implying that Klotho is renoprotective. Rats with AKI given recombinant Klotho had higher Klotho protein, less kidney damage, and lower NGAL than rats with AKI given vehicle. Hence, AKI is a state of acute reversible Klotho deficiency, low Klotho exacerbates kidney injury and its restoration attenuates renal damage and promotes recovery from AKI. Thus, endogenous Klotho not only serves as an early biomarker for AKI but also functions as a renoprotective factor with therapeutic potential.